A study to assess nutritional status and related factors among children of 6 months to 5 years in residing at field practice area of B. J. Medical Collage, Ahmedabad - Patel, Hely Bharatbhai; Patel, Vaishali Chandrakant; Patel, Hetal Y.; Parmar, Rajan K.; Patel, Alpesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Under nutrition continues to be an important public health problem, inspite of several nutrition intervention programs in India. The present study was carried out to know the prevalence of underweight, stunting and wasting among 6 months to 5 years children and to assess nutrition status and related factors among study population. Methods: A community based cross sectional study using stratified random sampling. Total 165 samples were taken from 5 field practice area of B. J. Medical College, Ahmedabad. From each area 33 random samples were taken. Results: Out of 165 children 80 and 85 were male and female. The prevalence of underweight, stunting and wasting was 45%, 46% and 29% respectively. SE class IV and V, low birth weight, higher birth order, late age of starting complementary feeding, parents education were significantly associated with undernutrition. Conclusions: The risk of undernutrition is higher in field practice area of B. J. Medical College, Ahmedabad. There is a need to strengthen promotion of maternal nutrition; maternal education and improving household socio-economic condition along with health care services may improve nutritional status of children.